004 Dispersion of refractoriness promotes arrhythmogenesis in a murine model of Brugada syndrome. (22nd September 2015) - Martin, C A; Grace, A A; Huang, C L-H
Abstract : Introduction: Recent experiments have implicated accentuated right ventricular (RV) transmural repolarization gradients in arrhythmogenesis in murine models of Brugada Syndrome. The present experiments investigated for the first time the involvement of heterogeneities in the corresponding ventricular effective refractory periods (VERP), hitherto assumed to vary in concert with action potential duration (APD). Methods: VERPs and APDs were compared in the right ventricular (RV) and left ventricular (LV), epicardial and endocardial, regions of Langendorff-perfused wild-type (WT) and loss of function Scn5a+/− murine hearts. APDs were obtained during regular pacing and VERPs from a programmed S1S2 protocol, before and following addition of flecainide or quinidine. VERP dispersions were calculated from the difference in VERP between neighbouring cardiac regions. Results: In contrast to APD values, Scn5a+/− hearts showed longer VERPs than WT. Both showed shorter VERPs in RV than LV epicardium and in the epicardia than endocardia of both LV and RV (Abstract 004 Figure 1 ). VERP/APD ratios were consistently larger in Scn5a+/− than WT but did not vary significantly between regions, contrasting with expectations from re-entrant arrhythmogenic mechanisms suggested previously for the gain of function, Scn5aΔ/+ genotype. However, Scn5a+/− hearts showed greater VERP dispersions, particularly across the RV, than WT. Both flecainide and quinidine increased the regional VERP values particularly in Scn5a+/− . However, flecainide increased but quinidine decreased the VERP dispersions, particularly across the RV in the Scn5a+/− (Abstract 004 Figure 2 ). This is in direct parallel with the established pro- and anti-arrhythmic effects of flecainide and quinidine experimentally and clinically. Conclusions: These findings implicate for the first time an involvement of VERP dispersions in the RV in the arrhythmogenesis found in murine Scn5a+/− hearts.